How was your day? A within-person analysis of how mental health may moderate the route from daily micro-events to satisfaction after work via affect and contextual performance - Junça Silva, A.; Caetano, A. (International Journal of Psychology, 2024)
This study builds on the affective events theory and the conservation of resources theory to propose a model that analyses an affect-to-behaviour-to-outcome route, highlighting how daily micro-events and subsequent affective reactions lead to behaviours (performance) and cognitions (satisfaction after work), and how mental health moderates this process. Results from a 5-day diary study, during the pandemic (N = 250, n = 1221), provided data to test the proposed affect-to-behaviour-to-outcome route. Poorer mental health buffered the positive within-person relationship between daily micro-events, affective reactions, performance and satisfaction after work, suggesting that high levels of mental health allowed individuals to maximise the benefits of positive daily micro-events in their satisfaction after work via affect and performance. This study presents original research analysing how situational factors create a route through which individuals experience affective reactions that influence their work behaviour, and in turn their levels of satisfaction after work.